ANALISIS KELAYAKAN USAHA IKAN ASIN SEPAT KERING (Tricoghaster, sp) DI KABUPATEN BANJAR KALIMANTAN SELATAN - Fenny Refiana; Yayuk Mintawahyuningsih; Ahmad Baparki (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The aim of the research was to find out the technical processing of dry salted sepat siam fish, to find out the costs, benefits, and feasibility obtained by entrepreneurs processing dried salted sepat siam fish, and to find out the problems faced. This research was conducted in Tambak Baru Village, Banjar District, Banjar District, South Kalimantan Province, namely in March 2023. The location for the research was determined based on the consideration that Tambak Baru Village, Banjar District, is a salted sepat fish processing center in Banjar Regency. This sampling method uses the Census method, namely sampling all salted fish processing entrepreneurs through surveys and direct interviews, the number of salted fish processing entrepreneurs in Tambak Baru Village, Banjar District, is 5 people. Technically, the dried salted fish business has been running with a production capacity of 134 kg at a price of IDR 65,000/kg. The biggest variable cost is the cost of raw materials with an average of Rp. 2,475,000/farmer Meanwhile, the fixed cost of the salted fish processing business is the equipment depreciation cost of Rp. 17,134/farmer. The average income is Rp. 8,710,000/farmer While the average profit of dried salted fish processing business is Rp. 4,417,866/farmer. The RCR value of the dried salted fish processing business was obtained at 2.029, which means every Rp. 1 invested in the dried salted fish processing business will generate Rp. 2,029 which means the business of processing dried salted fish is feasible